Major Risk Factors for Diabetic Retinopathy Complications in Type 2 Diabetes Mellitus: Faktor Risiko Utama Komplikasi Retinopati Diabetik pada Diabetes Melitus Tipe 2 - Rapael Ginting; Masryna Siagian; Cantika Viona Adytia Hutagalung; Cherin Lolenstine (Academia Open, 2025)
Background: Diabetes mellitus affects over 415 million people globally and is projected to reach 642 million by 2040, with diabetic retinopathy (DR) becoming a major cause of preventable blindness. Specific background: In Indonesia, DR prevalence remains high, yet early detection is often delayed, particularly in community and private clinic settings. Knowledge gap: Most studies on DR risk factors have been conducted in tertiary hospitals or general populations, while evidence from community-based ophthalmology clinics is limited. Aim: This study analyzed factors associated with DR complications among type 2 diabetes mellitus (T2DM) patients at Klinik Mata Vision Max. Results: Using a case–control design with 60 participants (30 cases, 30 controls), multivariate logistic regression revealed that uncontrolled blood glucose (OR = 7.5, p = 0.007), diabetes duration >5 years (OR = 6.4, p = 0.016), hypertension (OR = 4.5, p = 0.043), and male sex (OR = 3.97, p = 0.054) significantly increased the risk of DR, while diet showed no direct effect. Novelty: This is the first systematic case–control study in a community-based eye clinic in Indonesia addressing DR risk factors. Implications: Findings highlight the urgency of integrating DR screening into primary care, emphasizing glycemic control, hypertension management, and targeted patient education to reduce preventable blindness.Highlight : Uncontrolled blood glucose is the dominant factor. Age >45 years and DM duration >5 years increase risk. Hypertension is significantly associated with diabetic retinopathy. Keywords : Diabetes Mellitus, Diabetic Retinopathy, Risk Factors, Age, Hypertension